844. ARISAEMA HETEROCEPHALUM subsp. HETEROCEPHALUM: Araceae. (September 2016) - Murata, Jin
Summary: The three subspecies of Ariseama heterocephalum Koidz. from the Ryukyu islands are described, and subsp. heterocephalum is illustrated. The species is paradioecious and detailed descriptions of the male and female stages are given.